AL-IJMĀ‘ FI AL-TAFSIR MAKNA AL-FATĀ DALAM QS. AL-KAHFI: 60: ANALISIS KOMPARATIF TAFSIR MODERN DAN KONTEMPORER - Muhamad Khabib Imdad; Fitri Meliani (Yayasan Baitul Hikmah al-Zain, 2025)
This study examines the concept of ijma‘ fi al-tafsir regarding the term al-fata in QS. al-Kahfi [18]:60 from modern and contemporary exegetical perspectives. It aims to trace the consistency and transformation of the classical consensus identifying al-fata as Yusha‘ bin Nun. Using a qualitative approach and content analysis through library research, the study explores five major tafsirs: al-Wasith by Muhammad Sayyid Tantawi, Tafsir al-Sya’rawi by Muhammad Mutawalli al-Sya’rawi, Tafsir al-Azhar by Hamka, Tafsir al-Mishbah by M. Quraish Shihab, and Zahratu al-Tafasir by Abu Zahrah. The findings reveal that four exegetes affirm the classical consensus, while Abu Zahrah focuses on the lexical dimension without explicit identification. These results indicate that the application of ijmāʿ fi al-tafsir in modern–contemporary tafsir remains dynamic and contextually shaped by each exegete’s epistemological orientation.